Efficacy of winter–spring strategic control against Rhipicephalus (Boophilus) microplus infestations on cattle in an area with ecological conditions highly favourable for the tick in northeast Argentina - Nava, Santiago; Toffaletti, Jose Rodolfo; Morel, Nicolas; Guglielmone, Alberto; Mangold, Atilio Jose (Wiley, 2019)
This work was performed to test the efficacy of winter–spring control strategies against Rhipicephalus (Boophilus) microplus (Ixodida: Ixodidae) infestations on cattle in the area ecologically most favourable for the development of this tick in Argentina. Two control schemes using three and four annual applications of acaricides, respectively, were evaluated. Animals in Group 1 were treated with ivermectin 3.15% on day 0, fluazuron on day 34, and fipronil on day 85. Animals in Group 2 were treated with ivermectin 3.15% on day 0, fluazuron on day 34, flumethrin on day 85, and fipronil on day 114. Animals in Group 3 represented the control group. Both treatment schemes provided appropriate levels of efficacy against R. microplus and also prevented the occurrence of the major peak in the frequency of this tick in autumn. The two treatment schemes were similar in terms of efficacy and thus the addition of a fourth treatment does not seem to confer any further advantage. The results of this work indicate that these strategic control methods provide appropriate levels of control against R. microplus.